As diretrizes curriculares nacionais e os projetos pedagógicos dos cursos de graduação em direito da UFERSA e da UERN em Mossoró/RN sob a ótica do modelo spices de estratégias educacionais - Cavalcante, Ingrid Silva (Universidade Federal Rural do Semi-Árido, 2019)
This research turns to deal with the profiles of law degree courses at UFERSA and UERN in the municipality of Mossoró/RN, based on the speeches of the professors themselves who teach in these institutions. This is a relevant research because from the local point of view it can promote the reflection of the teams that form the law courses in the municipality of Mossoró in order to seek to strengthen the positive points of their courses or seek mechanisms to overcome possible unwanted failures, in order to contribute to the formation of professionals who will occupy the most diverse functions throughout the country, in this sense, it also has a relevance beyond the local one. For that, the present work seeks to discuss the construction of the concept of national curriculum guidelines in Brazil specifically in relation to the law course, as well as to evaluate the relevance of higher education assessment systems in Brazil in the context of the educational strategies model SPICES. The theoretical framework was based on the resolutions of the National Education Council about the national curricular guidelines for higher education, especially for the law course, not to mention the law of the foundations and guidelines of education, and the law that established the National System of Education. Higher Education Assessment (SINAES), as well as articles, dissertations, theses and books that deal with the dynamics of higher education in Brazil. The empiric research of the present work consists in conducting closed interviews with the teachers who build the researched universities. However, it was possible to observe from the qualitative analysis of the interviews that in practice the profiles of the courses differ from the proposed in their pedagogical project. Notwithstanding that despite having identical ideal objectives in the course projects, in practice, the courses made different policy choices by designing relatively different course profiles. Finally, it was concluded that the Brazilian educational system, as far as law courses are concerned, is still very much in a cast. Although the DCN points to spaces of freedom and autonomy, in reality there is little use of this creativity by the educational institutions, generating isomorphism, courses with PPC and very similar praxis, making it necessary to have a greater openness to a factual dialogic construction. Moreover, it is noteworthy that it is necessary to fortify the evaluation instruments in order to allow the paths traced by a certain course a constant reanalysis, so that the university can always recreate itself seeking a higher education. quality and can further address the needs of the people.
Monografia
Keywords: Direito; Diretrizes curriculares; Educação; SINAES; SPICES; UERN; UFERSA; Curriculum guidelines; Law; Education; CIENCIAS SOCIAIS APLICADAS::DIREITO